1991
DOI: 10.1073/pnas.88.4.1182
|View full text |Cite
|
Sign up to set email alerts
|

Sexual transmission of human T-cell leukemia virus type I associated with the presence of anti-Tax antibody.

Abstract: The tax gene product (Tax protein) of human T-cell leukemia virus type I (EHTLV-I) is a specific transcriptional activator of the viral long terminal repeat sequence and is essential for the replication cycle of the virus. To elucidate the relationship between the presence of anti-Tax antibody and the transmission of the viral infection, annual consecutive serum samples from married couples serologically discordant or concordant for HTLV-I were examined. These included 5 individuals whose spouses seroconverted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 37 publications
1
30
0
1
Order By: Relevance
“…Inoculation of rabbits with HTLV-1-infected cell lines derived from patients with ATL or HAM/TSP demonstrate the heterogeneity in the biological response to HTLV-1 infection (Lairmore et al, 1992). Immunization of rabbits with synthetic peptides verified immunodominant epitopes of the viral envelope protein (Env) (Lal et al, 1991;Tanaka et al, 1991) and also defined regions of Env important for antibody-dependent cell-mediated cytotoxicity (Chen et al, 1991). Soon after, it was demonstrated that peptide immunization with amino acids 190-199 of the Env protein could protect rabbits from subsequent HTLV-1 challenge, opening the possibility for vaccine development (Tanaka et al, 1994).…”
Section: Rabbit Modelsmentioning
confidence: 96%
“…Inoculation of rabbits with HTLV-1-infected cell lines derived from patients with ATL or HAM/TSP demonstrate the heterogeneity in the biological response to HTLV-1 infection (Lairmore et al, 1992). Immunization of rabbits with synthetic peptides verified immunodominant epitopes of the viral envelope protein (Env) (Lal et al, 1991;Tanaka et al, 1991) and also defined regions of Env important for antibody-dependent cell-mediated cytotoxicity (Chen et al, 1991). Soon after, it was demonstrated that peptide immunization with amino acids 190-199 of the Env protein could protect rabbits from subsequent HTLV-1 challenge, opening the possibility for vaccine development (Tanaka et al, 1994).…”
Section: Rabbit Modelsmentioning
confidence: 96%
“…Using a Western blot assay with a recombinant Tax protein as the antigen, Chen et al 89 tested serum samples from married couples who were serologically discordant or concordant for HTLV-1. The results revealed that 24 of 32 (75%) men within the concordant group (in which both the husband and wife were HTLV-1 carriers) had anti-Tax antibodies, whereas 5 of 18 (27.8%) men in the discordant group (in which the husband was a carrier and the wife was seronegative for HTLV-1) were positive for anti-Tax antibodies.…”
Section: Genital Excretion and Viral Transmission Of Htlvmentioning
confidence: 99%
“…However, preliminary data from our laboratory suggest that anti-rex CTL can be found in healthy carriers. Further, IgM and IgA antibodies directed against tax and env are found in HAM/ TSP patients and IgG specific for gag, tax and env are found in HAM/TSP and healthy carriers [17,18].…”
mentioning
confidence: 98%